Prospective evaluation of planar bone scintigraphy, SPECT, SPECT/CT, 18F-NaF PET/CT and whole body 1.5T MRI, including DWI, for the detection of bone metastases in high risk breast and prostate cancer patients: SKELETA clinical trial. (2nd January 2016) - Jambor, Ivan; Kuisma, Anna; Ramadan, Susan; Huovinen, Riikka; Sandell, Minna; Kajander, Sami; Kemppainen, Jukka; Kauppila, Esa; Auren, Joakim; Merisaari, Harri; Saunavaara, Jani; Noponen, Tommi; et al.
Abstract : Purpose. Detection of bone metastases in breast and prostate cancer patients remains a major clinical challenge. The aim of the current trial was to compare the diagnostic accuracy of 99m Tc-hydroxymethane diphosphonate ( 99m Tc-HDP) planar bone scintigraphy (BS), 99m Tc-HDP SPECT, 99m Tc-HDP SPECT/CT, 18 F-NaF PET/CT and whole body 1.5 Tesla magnetic resonance imaging (MRI), including diffusion weighted imaging, (wbMRI+DWI) for the detection of bone metastases in high risk breast and prostate cancer patients. Material and methods. Twenty-six breast and 27 prostate cancer patients at high risk of bone metastases underwent 99m Tc-HDP BS, 99m Tc-HDP SPECT, 99m Tc-HDP SPECT/CT, 18 F-NaF PET/CT and wbMRI+DWI. Five independent reviewers interpreted each individual modality without the knowledge of other imaging findings. The final metastatic status was based on the consensus reading, clinical and imaging follow-up (minimal and maximal follow-up time was 6, and 32 months, respectively). The bone findings were compared on patient-, region-, and lesion-level. Results. 99m Tc-HDP BS was false negative in four patients. In the region-based analysis, sensitivity values for 99m Tc-HDP BS, 99m Tc-HDP SPECT, 99m Tc-HDP SPECT/CT, 18 F-NaF PET/CT, and wbMRI+DWI were 62%, 74%, 85%, 93%, and 91%, respectively. The number of equivocal findings for 99m Tc-HDP BS, 99m Tc-HDP SPECT, 99m Tc-HDP SPECT/CT, 18 F-NaF PET/CT and wbMRI+DWI was 50, 44, 5, 6, and 4, respectively. Conclusion. wbMRI+DWI showed similar diagnostic accuracy to 18 F-NaF PET/CT and outperformed 99m Tc-HDP SPECT/CT, and 99m Tc-HDP BS.